PROSPECTS FOR IMPLEMENTATION OF BUILD OPERATE AND TRANSFER IN INDONESIA - Lira, M. Adnan (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
A form of cooperation between the government and business entities in providing infrastructure for the public interest by referring to specifications previously determined by the government or parties representing the government officially, where some or all of it uses resources owned by the business entity, taking into account the distribution of risks between the parties involved in the collaboration [1]. Government cooperation with business entities for infrastructure development is outlined in the Build-Openrate and Transfer (BOT) model. The research method that the author uses in this research is normative juridical, namely research that examines written legal norms by referring to related legal provisions. The prospect of implementing BOT in Indonesia legally can be carried out based on freedom of contract and good faith, new regulations by the government, and the opening of Indonesia in the era of globalization to contracts that have been accepted internationally. Economically, BOT can support and facilitate development and business activities, whether carried out by individuals, companies, or the government. The obstacles encountered in implementing BOT include the inadequate substance of statutory regulations and law enforcement practices, including unsupportive jurisprudence. Convoluted bureaucratic interference in the process of building public facilities, as well as the long BOT period, which allows for changes in the parties involved in the BOT, creates doubts for parties who have no experience as BOT recipients.